Tindak Tutur Guru pada Pembelajaran Bahasa Indonesia di SMA Santo Gerardus Mayella Kalembu Weri: Kajian Pragmatik - Kanisius Kami; Lasarus Bulu Kaleka; Konradus Doni Kelen; Kristiana Mahung; Rosalia Anggreni Ngongo (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to describe the speech acts of teachers in Indonesian language learning at Santo Gerardus Mayella Kalembu Weri High School through pragmatic studies. The type of research used in this study is descriptive qualitative research. The data source for this study is the Indonesian language teachers of Santo Gerardus Mayella Kalembu Weri High School. The data collection techniques used in this study are observation and documentation. The data analysis technique used is qualitative descriptive analysis with a pragmatic analysis approach to speech acts. through the following stages: data reduction, data classification, context analysis, data interpretation, and data presentation. The results of the study showed that there were teacher utterances classified based on types such as assertive (studying expository texts, explaining text structures, and providing information), directive (opening books, discussing, asking questions, and using polite language), expressive (praising, criticizing with some not paying attention, saying thank you), commissive (promising help, offering help, promising hope, offering learning facilities through the class WA group, promising feedback with comments, offering consultation opportunities in the library), declarative (stipulating by collecting assignments on Friday this week, allowing discussions with deskmates, prohibiting plagiarism in essay writing assignments).